2016
DOI: 10.1128/jvi.01127-16
|View full text |Cite
|
Sign up to set email alerts
|

Avian Leukosis Virus Activation of an Antisense RNA Upstream of TERT in B-Cell Lymphomas

Abstract: Avian leukosis virus (ALV) induces tumors by integrating its proviral DNA into the chicken genome and altering the expression of nearby genes via strong promoter and enhancer elements. Viral integration sites that contribute to oncogenesis are selected in tumor cells. Deep-sequencing analysis of B-cell lymphoma DNA confirmed that the telomerase reverse transcriptase (TERT) gene promoter is a common ALV integration target. Twenty-six unique proviral integration sites were mapped between 46 and 3,552 nucleotides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These integrations are the most clonally expanded in a subset of tumors, suggesting that proviral integration into this region is an important early event in lymphoma development [ 3 , 9 ]. Tumors with TERT promoter integrations are associated with increased TERT expression [ 7 , 8 ]. The mechanism of this activation is presently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These integrations are the most clonally expanded in a subset of tumors, suggesting that proviral integration into this region is an important early event in lymphoma development [ 3 , 9 ]. Tumors with TERT promoter integrations are associated with increased TERT expression [ 7 , 8 ]. The mechanism of this activation is presently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Proviral integration can upregulate the expression of proximal genes through enhancer and promoter elements in the viral long terminal repeat (LTR) sequences [ 1 , 2 ]. Previous studies have shown common integration sites in ALV-induced lymphomas near MYC , MYB , BIC and, more recently, the telomerase reverse transcriptase (TERT) genes [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Previously, we found that integrations in the TERT promoter region were one of the most clonally expanded—or most abundant unique—integrations in tumors tested from ALV infected chickens [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, loss of super-infection resistance could be involved in tumorigenesis. Alternatively, deletions in the env region of proviruses or mutations affecting env expression, identified in some tumors in previous work in our lab [ 18 ], might allow cells to overcome super-infection resistance.…”
Section: Discussionmentioning
confidence: 99%